Phasing via pure crystallographic least squares: an unexpected feature. Issue 2 (23rd February 2018) - Burla, Maria Cristina; Carrozzini, Benedetta; Cascarano, Giovanni Luca; Giacovazzo, Carmelo; Polidori, Giampiero
Abstract : Crystallographic least‐squares techniques, a fundamental tool for crystal structure refinement, are used for the first time for ab initio crystal structure solution. No help was needed from other phasing techniques, such as the calculation of electron‐density maps. Abstract : Crystallographic least‐squares techniques, the main tool for crystal structure refinement of small and medium‐size molecules, are for the first time used for ab initio phasing. It is shown that the chief obstacle to such use, the least‐squares severe convergence limits, may be overcome by a multi‐solution procedure able to progressively recognize and discard model atoms in false positions and to include in the current model new atoms sufficiently close to correct positions. The applications show that the least‐squares procedure is able to solve many small structures without the use of important ancillary tools: e.g. no electron‐density map is calculated as a support for the least‐squares procedure.